Earth’s and Mars’ atmospheres: an astrobiological approach - Rodrigues, Gustavo; Perucci Mostaro, Anthony Henrique (Cadernos de Astronomia, 2026)
This article compares the atmospheres of Earth and Mars from an astrobiological perspective, examining their evolution, composition, and the processes that determine habitability. For Earth, it discusses formation and climate regulation by the oceans and the sequestration of CO2 through sedimentation, the rise of an O2-rich atmosphere (the Great Oxidation Event, GOE), and the roles of N2, O2, and O3 in maintaining liquid water and supporting life. For Mars, it analyzes the current low-pressure, CO2-dominated atmosphere, atmospheric and water loss, the intensity of surface radiation, and the soil’s oxidizing chemistry that compromise the preservation of organic matter. The text emphasizes the complementarity between atmospheric studies and subsurface investigations, identifying subsurface refugia, with lower radiation doses and reduced chemical oxidation, as the most promising locations for biosignature preservation. The article adopts a didactic, integrative approach intended to help students and enthusiasts in astronomy and astrobiology understand the key processes that govern planetary habitability.